Framing Analysis of News Coverage on the “Free Nutritious Meal (MBG)” Program in Detik and Kompas (January 20–26, 2025) - Mardiana, Amalia Chaerani; Putri, K.Y.S; Prananingrum, E.N. (International Journal of Global Community, 2025)
The Free Meal Program was one of President Prabowo’s key initiatives during last year’s general election to reduce stunting rates among children across Indonesia. This program has initiated discussions among various segments of Indonesian society, as it has generated both support and criticism. One primary concern is the lack of targeted distribution, which could impact the 2025 budget. As a result, the media serves as a bridge between the government and the public and plays a crucial role in disseminating information to help society respond appropriately to this policy. This study examines how the media frame news coverage of the free meal program, focusing on three key aspects, including the milk menu policy, the budget expansion for the program, and the president’s directive on budget efficiency for 2025. The research analyses two of the most frequently accessed online news platforms in Indonesia, Kompas, and Detik, covering the period from January 20 to January 26, 2025. This study employs a qualitative research method using Robert Entman’s framing analysis. The findings indicate that Kompas presents a relatively critical and controversial framing of the Free meal program by providing detailed and comprehensive information. In contrast, Detik maintains a more neutral stance with general and concise reporting.